Fiber-based polarization-sensitive Fourier domain optical coherence tomography using B-scan-oriented polarization modulation method - 安野 嘉晃; Yamanari Masahiro; Makita Shuichi; Madjarova Violeta Dimitrova; Yatagai Toyohiko; Yasuno Yoshiaki (Optics Express, 2006)
Fiber-based high-speed polarization-sensitive Fourier domain optical coherence tomography (PS-FD-OCT) is developed at 840 nm wavelength using polarization modulation method. The incident state of polarization is modulated along B-scan. The spectrometer has a polarizing beamsplitter and two line-CCD cameras operated at a line rate of 27.7 kHz. From the 0th and 1st orders of the spatial frequencies along the B-scanning, a depth-resolved Jones matrix can be derived. Since continuous polarization modulation along B-scan causes fringe washout, equivalent discrete polarization modulation is applied to biological measurements. For the demonstration, an in vitro chicken breast muscle, an in vivo finger pad, and an in vivo caries lesion of a human tooth are measured. Three dimensional phase retardation images show the potentials for applying the system to biological and medical studies.